'One of the noblest inventions of the age': British steamboat numbers, diffusion, services and public reception, 1812 - c.1823. Issue 1 (1st June 2014) - Williams, David; Armstrong, John
Abstract : The operation of the Comet, Britain's first commercial steamboat, on the Clyde in 1812 led to a period of rapid steamboat development. Drawing on little utilised sources, this study examines the impact of the steamboat in its first decade. Diffusion was rapid and relatively nationwide embracing river, coastal and short sea services. The impact in terms of services, mostly passenger orientated (but also including towage), was considerable and contributed to a new, popular appreciation of steam technology and changes in lifestyles. How the press and government responded to this new technological advance is also considered. A brief conclusion points to the special nature of the steamboat's immediate impact in a wider context.